Data Envelopment Analysis of Helsinki-Tallinn Transportation Chains - Hilmola, Olli-Pekka (Promet - Traffic&Transportation, 2013)
The Baltic Sea shipping is at a crossroads as sulphur regulation will lead to excessive cost increases from the year 2015 onwards and CO2 emission trading is planned to be implemented for the entire shipping sector within the EU area. Therefore, shipping is going to be minimized and hinterland transportation (road and rail) will act as substitute. This research analyzes the situation on one of the highest volume general cargo transportation routes of Finland (operating between Helsinki, Finland and Tallinn, Estonia), including loading and unloading at seaports and short sea shipping activity in between. Based on the efficiency evaluation results, it seems that containers should be favoured over semi-trailers – containers could be carried efficiently either in container ships or even at currently favoured RoRo or RoPax ships. Our research illustrates that pure container shipping with larger container ships within the analyzed route is not entirely out of question, but lead time and hinterland operations should receive more attention. Alternatively, RoRo and RoPax ships can also do something to increase their competitiveness in environmental harm caused and diesel consumption – higher cargo loads and utilization levels are short-term key for continued dominance.